Pengaruh Stuktur Modal, Likuiditas dan Ukuran Perusahaan Terhadap Nilai Perusahaan pada Perusahaan Manufaktur Sektor Industri Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2018-2021 - Prastyatini, Sri Lestari Yuli; Tasekep, Hezron Sandy; Prabowo, Adia Adi (Universitas Batanghari Jambi, 2024)
This research aims to examine the influence of capital structure, liquidity and company size on company value in manufacturing companies in the food and beverage industry sector listed on the Indonesia Stock Exchange for the 2018-2021 period. The sampling technique in this research uses a purposive sampling method then the data is processed using SPSS. This research method uses quantitative research. The results of this research show that simultaneously the variables liquidity, asset structure and company size have a significant influence on company value in the food and beverage manufacturing industry listed on the Indonesia Stock Exchange for the 2018-2021 period. However, partially all variables in this research model have no influence on company value.